2011
DOI: 10.1103/physreva.83.062309
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and quantum phase transition in the one-dimensional anisotropicXYmodel

Abstract: In this paper the entanglement and quantum phase transition of the anisotropic s = 1/2 XY model are studied by using the quantum renormalization group method. By solving the renormalization equations, we get the trivial fixed point and the untrivial fixed point which correspond to the phase of the system and the critical point, respectively. Then the concurrence between two blocks are calculated and it is found that when the number of the iterations of the renormalziation trends infinity, the concurrence devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 36 publications
(33 reference statements)
3
39
0
Order By: Relevance
“…It reaches to maximum value at the critical point and it can be seen that this maximum value is smaller in three dimensions as compared to its two-dimensional counterpart. Likewise scenario can be seen for the qualitative and the quantitative behavior of the concurrence in the XY model, as we go from the lower to higher dimensions [10,31]. It is the monogamy that limits the entanglement shared among the number of neighbor sites [19].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…It reaches to maximum value at the critical point and it can be seen that this maximum value is smaller in three dimensions as compared to its two-dimensional counterpart. Likewise scenario can be seen for the qualitative and the quantitative behavior of the concurrence in the XY model, as we go from the lower to higher dimensions [10,31]. It is the monogamy that limits the entanglement shared among the number of neighbor sites [19].…”
Section: Introductionmentioning
confidence: 94%
“…1.) to obtain the effective Hamiltonian which has similar structure as that of the original Hamiltonian. From the previous studies of the XY model [10,11,31], it is found that in the renormalization process, the projection operator constructed from the degenerate ground states of the block works well for obtaining the effective Hamiltonian in the renormalized Hilbert space of spin -1/2 particle. The degenerate ground eigenstates can only be obtained if we consider the blocks containing odd number of spins in any spatial dimensions.…”
Section: Qrg Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Further,by applying the quantum renormalization-group (QRG) approach, M. Kargarian et al investigated the entanglement in the anisotropic Heisenberg model [21,22] and discussed the nonanalytic behaviors and the scaling close to the quantum critical point of the system. Recently We have calculated the block-block entanglement in the XY model without and with staggered Dzyaloshinskii-Moriya (DM) interaction by using this QRG method and have found the DM interaction can enhance the entanglement and influence the QPT of the system [23,24].…”
Section: Introductionmentioning
confidence: 99%